Wear and corrosion in medical applications - Markhoff Jana; Grabow Niels (Current Directions in Biomedical Engineering, 2020)
Biomaterials applied to replace or restore body functions are exposed to different mechanical forces and corrosion processes due to body fluids, which might result in the generation of corrosion products, wear debris and particles potentially leading to inflammation and inhibition or loss of function. This brief review will give a short overview about the processes of wear generation and corrosion, the occurrence of the respective wear products in different medical applications and their biological influences. Wear and corrosion are important factors that control and determine the long-term clinical performance of a biomaterial.